Annual Editions: Developing world - Griffiths,Robert J. (Dubuque McGraw-Hill/Dushkin, 2005)
Annual edtions :Developing World seeks to provide studentswith an understanding of the diversity and comlexity of the developing world and acquaint them with the challenges that these nations confront.
Keywords: Developing world